2016
DOI: 10.1523/jneurosci.0217-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Molecular Markers and Soma Size of Inhibitory Neurons: Evidence for Four Subtypes of GABAergic Cells in the Inferior Colliculus

Abstract: Inhibition plays an important role in shaping responses to stimuli throughout the CNS, including in the inferior colliculus (IC), a major hub in both ascending and descending auditory pathways. Subdividing GABAergic cells has furthered the understanding of inhibition in many brain areas, most notably in the cerebral cortex. Here, we seek the same understanding of subcortical inhibitory cell types by combining staining for two types of extracellular markers-perineuronal nets (PNs) and perisomatic rings of termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 50 publications
6
87
0
Order By: Relevance
“…Although the expression of PNN and its association with specific cell types have been well characterized in rodent visual and somatosensory cortex (Pizzorusso et al, 2002; McRae et al, 2007; Liu et al, 2013; Takesian and Hensch, 2013) and subcortical auditory areas (Beebe et al, 2016), the expression patterns in A1 are only beginning to be described (reviewed in Sonntag et al, 2015). The relationship between PV and PNN expression in A1 has not been previously characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Although the expression of PNN and its association with specific cell types have been well characterized in rodent visual and somatosensory cortex (Pizzorusso et al, 2002; McRae et al, 2007; Liu et al, 2013; Takesian and Hensch, 2013) and subcortical auditory areas (Beebe et al, 2016), the expression patterns in A1 are only beginning to be described (reviewed in Sonntag et al, 2015). The relationship between PV and PNN expression in A1 has not been previously characterized.…”
Section: Discussionmentioning
confidence: 99%
“…IC GABAergic neurons can be classified into four types using the presence/absence of VGLUT2+ axosomatic rings and perineuronal nets (Beebe et al . ), and in the study, the authors found that the majority of GABAergic neurons without axosomatic rings (i.e. SG cells) are not covered with perineuronal nets, whereas most LG neurons were covered with perineuronal nets, suggesting a difference in plastic ability between SG and LG cells.…”
Section: Discussionmentioning
confidence: 79%
“…; Beebe et al . ). Recently, Goyer and colleagues () found a subgroup of GLU cells which express VIP, have a less‐flat dendritic field, and show a gradient of intrinsic membrane properties inside the ICC.…”
Section: Discussionmentioning
confidence: 97%
“…GABAergic IC neurons were shown to be classified based on their cell body size (Ito et al, ; Beebe et al, ). We therefore measured the perimeter of two types of GABAergic neurons in young adult mice: PV + /NOS − /GAD67 + neurons (DC, n = 74 cells; LC, n = 79 cells; ICC, n = 78 cells) and PV + /NOS + /GAD67 + neurons (DC, n = 13 cells; LC, n = 15 cells; ICC, n = 75 cells).…”
Section: Resultsmentioning
confidence: 99%
“…6A): PV 1 /NOS 2 / GAD67 1 neurons, PV 1 /NOS 1 /GAD67 1 neurons, PV 1 / NOS 2 /GAD67 2 neurons, and PV 2 /NOS 1 /GAD67 2 neurons. In all three subdivisions of the IC, the largest population was PV 2 /NOS 1 /GAD67 2 neurons ( GABAergic IC neurons were shown to be classified based on their cell body size (Ito et al, 2009;Beebe et al, 2016). We therefore measured the perimeter of two types of GABAergic neurons in young adult mice: PV 1 /NOS 2 /GAD67 1 neurons (DC, n 5 74 cells; LC, n 5 79 cells; ICC, n 5 78 cells) and PV 1 /NOS 1 / GAD67 1 neurons (DC, n 5 13 cells; LC, n 5 15 cells; ICC, n 5 75 cells).…”
Section: Comparisons Of the Four Types Of Ic Neurons Defined By Pv Nmentioning
confidence: 99%